2021
DOI: 10.1371/journal.pone.0250973
|View full text |Cite
|
Sign up to set email alerts
|

Differential parasitism by four species of phorid flies when attacking three worker castes of the leaf-cutting ant Atta laevigata (Smith, 1858)

Abstract: Certain species of parasitic flies belonging to the Phoridae are known to attack Atta spp. workers foraging along trails, near nest openings used by the ants to supply the colony with plant material, and in the areas where the ants are actively cutting plant material. However, there have been no previous studies of phorid parasitism of non-foraging worker ants, for example excavators and soldiers. Excavators can be found on the surface around specialized nest openings, carrying and dumping soil on characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Three to five was a frequent number of A. attophilus flies emerging from parasitized ants, but some host produced up to 17 flies. The highest number of flies by host ever reported in A. laevigata was 14 (Souza et al, 2021; Bragança, 2011), but 17 flies has already been reported for A. sexdens (Galvão et al, 2019). Bragança et al (2016) reported cases of A. laevigata foragers simultaneously parasitized by A. attophilus and A. vicosae (0.0055%); however, we detected no case of multiparasitism.…”
Section: Discussionmentioning
confidence: 96%
“…Three to five was a frequent number of A. attophilus flies emerging from parasitized ants, but some host produced up to 17 flies. The highest number of flies by host ever reported in A. laevigata was 14 (Souza et al, 2021; Bragança, 2011), but 17 flies has already been reported for A. sexdens (Galvão et al, 2019). Bragança et al (2016) reported cases of A. laevigata foragers simultaneously parasitized by A. attophilus and A. vicosae (0.0055%); however, we detected no case of multiparasitism.…”
Section: Discussionmentioning
confidence: 96%
“…The study of host-parasitoid interactions in leaf-cutting ants is more complex than that seen in most other insects. Leaf-cutting worker ants are grouped into castes, displaying polymorphism and performing different tasks in the colony, which can influence parasitism rates by phorids [34]. Furthermore, leaf-cutting ant larvae present in the nests have a wide range of sizes, which, as seen here, could influence the number of eggs laid in each host.…”
Section: Discussionmentioning
confidence: 90%
“…Leaf-cutting ants transiting foraging trails and working in the areas where the leaves are being cut are subject to parasitism by several species of phorid flies (Diptera: Phoridae). These parasitoids oviposit in the head or abdomen of their hosts (Bragança, 2011;Bragança et al, 2016;Farder-Gomes et al, 2018;Souza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that large worker ants are preferentially attacked by phorid species that are themselves comparatively larger than other phorid species, while smaller workers are more frequently attacked by smaller parasitoids (Bragança et al, 1998;Elizalde & Folgarait, 2011;Farder-Gomes et al, 2018;Tonhasca Jr. et al, 2001). For example, Eibesfeldtphora phorids are relatively large flies that preferentially parasitize the largest A. laevigata and Atta bisphaerica Forel workers, while the smallest workers are parasitized by smaller phorids such as M. grandicornis (Bragança et al, 2021;Souza et al, 2021). Bragança et al (2021) studied four colonies of A. bisphaerica.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation